ATTITUDE TOWARDS ENGLISH LANGUAGE LEARNING (A Survey on the Rural Students of SMAN 2 Paloh) - Setianengsih, Eris; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe aim of this study was to investigate the rural students’ attitude towards English language learning in term of affective, behavioral and cognitive aspect. In order to collect data, a language questionnaire was designed with thirty closed questions. The questions were put in Likert Scale and focused on the repertory grid technique for studying attitudes towards school subject. The grid was interest, difficulty, freedom of expressing idea and social benefit that connected with three aspects of attitude. The study took place at one of rurals School in Paloh, Sambas regency. The participants were fifty-five students from grade tenth and eleventh at SMAN 2 Paloh. This study was conducted using a survey method. In the end of the study, the collected data analyzed by using formulas designed for attitude. Based on the calculation, the mean score for the affective aspect was reached 76.25%, behavioral was 60.76% and cognitive was 67.82%. Based on the interpretation score, the students’ result ranked positive. In conclusion, the rural students’ of SMAN 2 Paloh have positive attitude towards English language learning in term of affective, behavioral, and cognitive aspects. Keywords: Attitude, Affective, Behavioral, cognitive, Language Learning, Rural Students